2022
DOI: 10.1186/s12951-022-01718-w
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative impacts of polymeric and metallic nanoparticles on cisplatin-induced nephrotoxicity: a 2011–2022 review

Abstract: Cisplatin (CDDP) is a well-known platinum-based drug used in the treatment of various malignancies. However, the widespread side effects that this drug leaves on normal tissues make its use limited. Since cisplatin is mainly eliminated from the kidneys, CDDP-induced nephrotoxicity is the most significant dose-limiting complication attributed to cisplatin, which often leads to dose withdrawal. Considering the high efficiency of cisplatin in chemotherapy, finding renoprotective drug delivery systems for this dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 120 publications
0
6
0
Order By: Relevance
“…88 Recent studies related to nanotechnology have also focused on new approaches to either preserve mitochondrial functions or promote mitochondrial biogenesis to ameliorate nephrotoxicity induced by cisplatin exposure. 84,89 Our previous study has confirmed that Se supplementation in the form of nanomaterials effectively promoted mammalian mitochondrial functions. 90 In the present study, we also found that the mitochondria dysfunctions and the subsequent nephrotoxicity consequences of mitochondrial dysfunctions in the NaAsO 2 exposed mice renal tissues and HK2 cells were effectively ameliorated by the SeNPs supplementation.…”
Section: Dovepressmentioning
confidence: 85%
See 1 more Smart Citation
“…88 Recent studies related to nanotechnology have also focused on new approaches to either preserve mitochondrial functions or promote mitochondrial biogenesis to ameliorate nephrotoxicity induced by cisplatin exposure. 84,89 Our previous study has confirmed that Se supplementation in the form of nanomaterials effectively promoted mammalian mitochondrial functions. 90 In the present study, we also found that the mitochondria dysfunctions and the subsequent nephrotoxicity consequences of mitochondrial dysfunctions in the NaAsO 2 exposed mice renal tissues and HK2 cells were effectively ameliorated by the SeNPs supplementation.…”
Section: Dovepressmentioning
confidence: 85%
“… 8 Mitochondria dysfunctions mediated nephrotoxicity has been heavily studied over past decades but continues to produce new and exciting findings. 84 Under pathological disorders, mitochondria dysfunctions triggered the damaged integrity of mitochondrial membrane potential (MMP), in turn, potentiating the release of a variety of mitochondrial components from the impaired mitochondrial into the cytoplasm or extracellular environment and promoting downstream oxidative stress, fibrosis, and inflammatory response cascades. 85 , 86 Moreover, the endonucleases from the mitochondria due to the hyperpermeable mitochondrial membranes translocate to the nuclei and cause DNA fragmentation.…”
Section: Discussionmentioning
confidence: 99%
“…The renal toxicity caused by cisplatin treatment can be successfully treated with polymeric and metallic nanoparticles that mostly act as inhibitors of oxidative stress and scavengers of generated free radicals. This could be found in the overview study by Davoudi et al [62]. Moreover, lately, synthesized ROS-responsive nanoparticles with "on demand" spatiotemporal release loaded with astaxanthin showed quite promising results in the treatment of oxidative stress during cisplatin-induced ototoxicity [63].…”
Section: Potential Strategies To Minimize Oxidative Damagementioning
confidence: 86%
“…The most major side effect of cisplatin is nephrotoxicity since it is primarily excreted from the kidney. By causing oxidative stress, inflammation, mitochondrial malfunction, and apoptosis, cisplatin damages the kidneys [ 37 ]. We assessed the extent of kidney injury by measuring the expressions of the apoptosis-related proteins caspase-3 and BAX.…”
Section: Discussionmentioning
confidence: 99%